Patterns of Family Communication in Preventing Grieving in Children whose Mothers Become Female Workers in Cibedug Village, Rongga District, West Bandung Regency - Septia, Ririn (Berumpun: International Journal of Social, Politics, and Humanities, 2023)
The presence of Indonesian female employees overseas yields both advantageous and unfavorable consequences. The potential beneficial effect has the potential to enhance the nation's foreign exchange reserves. Nevertheless, there are adverse consequences that manifest in the shape of diverse challenges, encompassing numerous instances of migrating laborers. The individuals in question have encountered instances of violence, as well as instances where their earnings were not remunerated, among other related matters. The aforementioned issues also manifest in the offspring they leave in their wake. The function of the mother is crucial for the development of children. Consequently, individuals would encounter a substantial detriment that would subsequently impact the trajectory of their attitudes and behaviors throughout their lifetimes. The objective of this study is to examine the role of family communication patterns in mitigating the grief stages experienced by children whose moms engage in migrant employment. The present study employs a qualitative research methodology, namely a case study approach. The focus of this study is on families residing in Cibedug Village, Rongga District, West Bandung Regency, who are responsible for rearing children while the mothers work as migrant workers. The findings of the study indicate that when democratic communication patterns are present within the family, children are able to navigate the stages of grief effectively. In contrast, families that employ authoritarian communication patterns pose challenges for children in effectively navigating the stages of grief, resulting in manifestations of irritability, introversion, mistrust, and limited ability to engage in social interactions with their peers.